Adenomyoma As A Lead Point For Jejunal Intussusception In An Adult: A Rare Case - Nakarmi, Rajiv; Shrestha, Muza; Maharjan, Sundar; Paudel, Deliya; Regmi, Himanshu (Journal of Society of Surgeons of Nepal, 2023)
Adenomyoma of small intestine causing intussusception in adults is a rare condition. The small intestine is the second most frequent location, usually in the periampullary area, but the lesion also occurs in the jejunum and ileum.We present a case of 76 years old female who presented with pain abdomen and was diagnosed to have jejunal intussusception. She underwent surgery with segmental resection and anastomosis of jejunum and the histopathological examination revealed jejunal adenomyoma as the pathological lead point. Adenomyoma of jejunum as a lead point should be taken into consideration while dealing with a patient with jejunal intussusception.